Mechanical and contact guidance properties of live cortical neurons in vitro measured via atomic force and fluorescent microscopy - Simon, Marc. (2017)
Abstract: Neurons are highly specialized cells that are the main building blocks of the nervous system. Neurons work together in complex networks to send, receive, store, and communicate information electrically and biochemically. In the developing vertebrate, neurons form connections with other neurons and cells to build the nervous system. They do this by extending processes called neurites. At the distal end of a neurite is a sensing structure called the growth cone, which has the ability to sense and respond to chemical, mechanical, and topographic cues, a process called neuron guidance. In this thesis we explore the mechanism of neuronal guidance by performing atomic force and fluorescence measurements. Specifically, we study the angular growth of neurites over time on three different types of polydimethylsiloxane surfaces imprinted with parallel ridges with ~ 0.8μm, ~ 1.6μm, and ~ 3.3μm spaced parallel ridges and stud. We observe maximum parallel alignment with surface features with surface 1, followed by surface 2, and surface 3, and maximum perpendicular alignment with surface 1, followed by surface 2, and surface 3. Additionally, the stiffness of cells can be an indicator of cell health, function, and biopolymer arrangements. Most cells have a protective polymer brush layer that shields the cell from mechanical damage and allows other cells to adhere it. We perform the first mechanical measurements of the neuronal polymer brush layer using atomic force microscopy (AFM) indentation techniques, and delineate its properties from the underlying soma. Our measurements reveal the cell body is an elastic material, 3-4 times stiffer than previously reported, and surrounded by a viscoelastic polymer brush layer. We show this brush layer is much softer than the cell body, and accounts for the previously reported viscoelastic properties of neurons. We also use AFM to measure mechanical and topographical properties of novel biomaterials that can be used as substrates for neuronal growth. Understanding the mechanical properties of neurons and their contact guidance properties is of great fundamental importance, and can also lead to better cellular modeling, new regenerative therapies and devices for nerve and brain regeneration, and safer and more effective surgeries and recoveries.; Thesis (Ph.D.)--Tufts University, 2016.; Submitted to the Dept. of Physics.; Advisor: Cristian Staii.; Committee: Roger Tobin, Peggy Cebe, and Austin Napier.; Keyword: Physics.